2021
DOI: 10.5306/wjco.v12.i7.522
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of thymoquinone in combination therapy against cancer and cancer stem cells

Abstract: The long-term success of standard anticancer monotherapeutic strategies has been hampered by intolerable side effects, resistance to treatment and cancer relapse. These monotherapeutic strategies shrink the tumor bulk but do not effectively eliminate the population of self-renewing cancer stem cells (CSCs) that are normally present within the tumor. These surviving CSCs develop mechanisms of resistance to treatment and refuel the tumor, thus causing cancer relapse. To ensure durable tumor control, research has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 148 publications
2
11
0
Order By: Relevance
“…Our findings agree with many prior studies that have shown anti-cancer activities for TQ [24][25][26][27][28][29]42,43 and Met [17][18][19][20][21][22][23] against CRC by inducing cell cycle arrest and apoptosis, modulating the PI3K/mTOR/HIF1α pathway, promoting glucose oxidation, and increasing ROS production. Our data also correlate and support the findings of earlier studies that reported enhanced anti-cancer effects by adding Met 23,33 or TQ 28,32 with 5-FU for the treatment of CRC, as well as by combining both agents for treating other malignancies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings agree with many prior studies that have shown anti-cancer activities for TQ [24][25][26][27][28][29]42,43 and Met [17][18][19][20][21][22][23] against CRC by inducing cell cycle arrest and apoptosis, modulating the PI3K/mTOR/HIF1α pathway, promoting glucose oxidation, and increasing ROS production. Our data also correlate and support the findings of earlier studies that reported enhanced anti-cancer effects by adding Met 23,33 or TQ 28,32 with 5-FU for the treatment of CRC, as well as by combining both agents for treating other malignancies.…”
Section: Discussionsupporting
confidence: 93%
“…17,18,20 Similarly, TQ halted cancer progression by inhibiting cell survival (e.g., survivin) and increasing pro-apoptotic (e.g., BAX, caspases) molecules in many malignancies, including CRC. 28,42,43 Furthermore, TQ induced apoptosis in cancer cells by promoting glucose oxidative phosphorylation following inhibition of LDHA enzyme, enhancing ROS production with declines in antioxidants, and downregulating the PI3K/mTOR/HIF1α network. [24][25][26][27][28][29] Further studies have also reported that combining 5-FU with TQ 28,32 or Met 23,33 resulted in boosted in vitro and in vivo anti-cancer actions against CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent reports, including the current study, indicated promising chemo-modulatory actions of TQ when combined with other chemotherapeutic agents used against various cancers [ 42 , 43 ]. In 2020, it was reported that TQ enhanced docetaxel efficiency in MDA-MB-231 and MCF-7 cells by reducing its effective dose [ 44 ].…”
Section: Discussionmentioning
confidence: 91%
“…Studies investigating the effect of TQ on CSCs are very few. Recent studies have shown that combining TQ with chemotherapeutic agents or natural compounds enhances inhibition of CSCs [55][56][57]. The combined treatment of TQ and emodin enhanced eradication of CD44+/CD24− CSCS population, when compared to either treatment alone.…”
Section: Discussionmentioning
confidence: 99%